Taxonomic implications of pollen of some species of the genus Pterospermum Schreb. (Malvaceae s.l. subfam. Dombeyoideae) - Ahmad Juhari, Muhammad Amirul Aiman; Talip, Noraini; Che Amri, Che Nurul Aini; Mohamad Basir, Nur Syazwani; Abdul Rahman, Mohamad Ruzi; Zohari, Ahmad Fitri; Ghazali, Mohd Norfaizal; Abdullah Siam, Nordahlia (Sociedade Botanica do Brasil, 2021)
A palynological study of six species of Pterospermum was conducted to investigate variation in pollen micromorphological characteristics. The studied species were P. diversifolium, P. elongatum, P. jackianum, P. javanicum, P. lanceifolium and P. subpeltatum. Pollen was subjected to acetolysis, single-grain techniques and dehydration series, and observed using light and scanning electron microscopy. The results reveal some common characters shared by all the studied species, namely: echinate-granulate exine ornamentation; porate pollen class; and circular amb. Variation was found in the ratio of exine thickness, pollen size, and average spine length, outline, shape, measurements, spine size and the presence of an annulus. These characters proved to be valuable for identifying and differentiating the studied species. This study shows that morphological characteristics of Pterospermum pollen have taxonomic value, especially for the identification and differentiation of species of the subfamily Dombeyoideae and even other Malvaceae s.l.